Sosialisasi Peningkatan Kesadaran Masyarakat Tentang Pengelolaan Sampah Di Desa Alukh Bakhu Kabupaten Aceh Tenggara - Mutiara Hikmah (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Waste is material that has no value or is worthless for ordinary or primary purposes in the manufacture or use of damaged or defective goods in manufacturing or excess or rejected or discarded material. In the provisions of Article 2 paragraph 1, it is also stated that waste managed under the law can consist of: 1) household waste, 2) waste similar to household waste, and 3) specific waste. Community Service (PKM) Socialization to Increase Community Awareness About Waste Management in Alukh Bakhu Village, Southeast Aceh Regency was carried out on 9-11 February 2024, totaling 45 people. Socialization is provided regarding waste and types of waste, sorting productive non-organic waste and special waste, waste management steps, the impact of throwing waste anywhere and sorting waste using 3R. To maintain environmental sustainability, an active role is needed, community participation (not only individuals, most of whom are housewives as the target of activities), support, and collaboration between industry and academic partnerships to encourage the development of waste storage management and its positive contribution to the environment.